SIGNIFIKANSI DIALOG ANTAR AGAMA DALAM ERA RADIKALISASI - sholahuddin sholahuddin (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2012)
After September eleventh, the face of Islam in the global world was dominated by the fundamentalism. In this paper, trough the data finding from the report of religious freedom issued by the Centre for Religious and Cross-Cultural Studies (CRCS), its shows that in 2010 the distribution of religious conflict was 21 cases (53%) located in West Java followed by the DKI Jakarta 6 cases (15%), North Sumatra 3 cases (15%) and East Java 2 cases (5%) followed by Central Java, Bali, Kalimantan Timur and Papua. From this the writer inverted that the conflict is concentrated in East Java. From that point, the writer elaborate the significance of inter-religious dialogues based on the Islamic doctrine and principle. In the era of radicalization one methods or way to minimize the prejudice that exist under the consciousness of the people is through dialogue.